Formulation of a Strategic Plan and Operational Plan for a Maternal Telehealth Startup: A Case Study of Hallo Mama - Steffani Anggraita Sari; Rhian Indradewa; Dimas Angga Negoro; Rian Adi Pamungkas (Journal of Management and Creative Business, 2026)
This study examines the formulation of a strategic plan and an operational plan for Hallo Mama, a maternal telehealth startup in Indonesia. Using a descriptive case study approach, the strategic plan was analyzed through the Input–Matching–Decision Stage framework, including the External Factor Evaluation (EFE), Internal Factor Evaluation (IFE), Competitive Profile Matrix (CPM), SWOT analysis, Internal–External (IE) Matrix, and Quantitative Strategic Planning Matrix (QSPM). The operational plan was designed around establishment stages, service process design, operations delivery, staffing requirements, service supply chain, and cost projections. The QSPM analysis identifies Market Penetration as the priority strategy with a Total Attractiveness Score (TAS) of 5.74, while Differentiation Focus is selected as the most appropriate competitive positioning. The operational plan is translated into a comprehensive service blueprint, tiered Basic and Premium service packages, a structured service supply chain model, and five-year OPEX and CAPEX projections totaling IDR 828,500,000 in capital expenditure within a maximum operating capital budget of IDR 2,000,000,000. The findings provide practical and managerial insights into the application of strategic management and operational planning for digital health startups in Indonesia, particularly those operating in maternal healthcare, postpartum care, and digital-doula services, while offering a scalable business model for sustainable growth and service quality improvement.